The Effectiveness of Guided Discovery in Distance Learning to Improve Scientific Literacy Competencies of Primary School Students - Anggriani, Agustin; Sarwi, Sarwi; Masturi, Masturi (Universitas Negeri Semarang, 2020)
This study aims is to determine the effectiveness of the guided discovery model in distance learning to improve students' scientific literacy competencies. The method used in this study was an experimental method with a pretest-posttest one group design. The research subjects were fifth grade students from three schools — Primary School A, Primary School B, and Primary School C — in Kudus Regency, Central Java, Indonesia. Sampling was determined using purposive sampling technique. Data collection techniques used scientific literacy tests. The data analyses used were paired sample t-test, one-way ANOVA test and n-gain test. The results of the paired sample t-test showed that there were significant differences in the mean scores of scientific literacy competences before and after the guided discovery model was applied. The one-way ANOVA test showed that there was a significant difference in the mean score between the three primary schools studied. Students at Primary School B, located in suburban area, scored the highest on average in scientific literacy competencies, followed by Primary School C students in urban area and Primary School A students in remote area. Based on the n-gain test, two primary school has high criteria with score 0.74 and 0.73 for school B and C, respectively. And the other one has moderate criteria for School A with n-gain score is 0.59. That means, guided discovery model is effective to improve the scientific literacy competencies on primary school student in Kudus Regency, Central Java, Indonesia.